(untitled) (Práxis Educativa, 2024)
This article embrace counter-hegemonic educational perspectives in their daily practice, addresses the theoretical perspective of intercultural education and presents educational experiences that seek to escape the process of standardization and homogenization in which traditional formal education is often involved. Thus, anchored in dialogues with the Popular Projects, it presents experiences that, with social movements, articulate responses to the contemporary social and educational crisis. In theoretical terms, it discusses the perspective of the school in context, i.e. the school contextualized territorially and culturally. The research is qualitative and is based on methodologies that have dialogism as a principle. Finally, we conclude that the practices of political organization generated by social movements are torches for the construction of counter-hegemonic educational projects and practices. Keywords: Counter-hegemony. Emancipation. Social movements. Right to education.